Simulation study of microscopic bubbles in amorphous alloy Co81.5B18.5 - Pham, Huu Kien (H. : ĐHQGHN, 2017)
Simulation of the diffirsion mechanism via microscopic bubbles in amorphous materials is carried out using the statistical relaxation models Cos.5Bft.5 containing 2 x 105 atoms. The present work is focused on the role of these bubbles for self-diffirsion in amorphous solids. It was found that the numbers'of the vacancy bubbles in amorphous Cog1."B1g ,b vary from 1.4 x 10-3 to 4 x 10-3 per atom depending on the relaxation degree. The simulation shows the collective character of the atomic movement upon diffirsion atoms moving. Due to the large size in comparison with B atom, the jump of a Co diffirses atom leads to a significant local rearrangement of the atoms located near the VB. Meanwhile, B diffuses like the movement of an interstitial impurity through the boron-VB. Diffirsion coeffrcients have been calculated via the vacancy bubbles and they are consistent with experimental data. The effect of the relaxation is also investigated and interpreted as a result of vacancy-bubble annihilation during thermal annealing.